Emotional Consequences of Collective Action Participation: Differentiating Self-Directed and Outgroup-Directed Emotions - Becker, Julia C.; Tausch, Nicole; Wagner, Ulrich (Personality & social psychology bulletin, 2011)
The present research examines the emotional and behavioral consequences of collective action participation. It demonstrates that “positive” and “negative” emotions can be experienced simultaneously as a result of collective action participation, yet it is important to distinguish outgroup-directed from self-directed emotions. Results of two experiments (N = 71 and N = 101) that manipulated participation in collective action illustrate that whereas collective action participants experience more outgroup-directed anger and contempt, they feel more self-directed positive affect. Furthermore, collective action participation predicted willingness to engage in moderate and radical collective actions in the future. These relations were mediated by outgroup-directed, but not by self-directed, emotions, suggesting that outgroup-directed rather than self-directed emotions play a crucial role in the maintenance of protest behavior. Theoretical and practical implications of these findings are discussed.